Finnish Yearbook of International Law, Volume 22, 2011 / Vol. 22, 2011. - Ius Gentium r.y. (Oxford ; Portland, Or. : Hart Pub., 2013)
"The Finnish Yearbook of International Law aspires to honour and strengthen the Finnish tradition in international legal scholarship. Open to contributions from all over the world and from all persuasions, the Finnish Yearbook stands out as a forum for theoretically informed, high-quality publications on all aspects of public international law, including the international relations law of the European Union. The Finnish Yearbook publishes in-depth articles and shorter notes, commentaries on current developments, book reviews and relevant overviews of Finland's state practice. While firmly grounded in traditional legal scholarship, it is open for new approaches to international law and for work of an interdisciplinary nature. The Finnish Yearbook is published for the Ius Gentium Association (the Finnish Society of International Law) by Hart Publishing. Earlier volumes may be obtained from Martinus Nijhoff, an imprint of Brill Publishers. Further information may be found at www.fybil.org."--Bloomsbury Publishing.
Unidentified Victims of Sex-Trafficking and Foucauldian Biopower: a Study on (Finnish) Anti-Trafficking Discourses and Practices Reclaiming Revolution; Book Reviews & Review Articles; Disobeying the Security Council: Counter measures against Wrongful Sanctions by Antonios Tzanakopoulos.; New Finnish Doctoral Dissertationsin International Law; An Axiom of Military Law:Applicability of National Criminal Law to Military Personneland Associated Civilians Abroad; Ius Gentium Association.
"Ius Gentium Association."
Includes bibliographical references.
Keywords: International law; International criminal court; Criminal procedure (International law); Criminal procedure (International law); International law; Finland; Finland